Modern information-communication technologies in education - Tursunxanov, Baxtdjan (MMIT Proceedings, 2025)
In this article we have discussed the role and significance of modern information and communication technologies (ICT) in the field of education. In it, we considered the benefits of effective use of ICT tools, digital resources, online learning platforms, e-textbooks, interactive teaching methods and educational technologies based on artificial intelligence.